A unique homozygous WRAP53 Arg298Trp mutation underlies dyskeratosis congenita in a Chinese Han family - Yingqi Shao; Sizhou Feng; Jinbo Huang; Jiali Huo; Yahong You; Yizhou Zheng (BMC, 2018)
Abstract Background Dyskeratosis congenita (DC) is an inherited telomeropathy characterized by mucocutaneous dysplasia, bone marrow failure, cancer predisposition, and other somatic abnormalities. Cells from patients with DC exhibit short telomere. The genetic basis of the majority of DC cases remains unknown. Methods A 2 generational Chinese Han family with DC was studied using targeted capture and next-generation sequencing to identify the underlying DC-related mutations. Results In this study, we identified a unique homozygous WD repeat containing antisense to TP53 (WRAP53) Arg298Trp mutation in the proband with DC and heterozygous WRAP53 Arg298Trp mutations in his asymptomatic, consanguineous parents and his sister, indicating an autosomal recessive inheritance mode. The proband with the homozygous WRAP53 Arg298Trp mutation had short telomere, classic clinical symptoms, and no response to danazol, glucocorticoid or cyclosporin A. Conclusions Thus, we reported for the first time that a unique homozygous WRAP53 mutation site underlies the development of DC.